Capacity of AIDS service organisations in Connecticut to respond to intimate partner violence. - Prust, Margaret L; Mellor-Crummey, Lauren; Sullivan, Tami P; Lang, Shawn; Hansen, Nathan B (Health & social care in the community, 2015)
Although intimate partner violence (IPV) is prevalent among women living with HIV and negatively impacts their health, few studies have examined the ability of AIDS service organisations (ASOs) to address IPV. This study used a qualitative approach to identify facilitators of and barriers to addressing IPV in female clients of ASOs in the United States. In-depth interviews were conducted between March and August 2011 with 20 ASO staff members and 19 female clients who reported a current or past history of IPV. Interviews were audio recorded, transcribed and analysed using the constant comparative method. These data identify barriers to addressing IPV at the organisation, provider and client levels, and include suggestions from both clients and providers about improving access to care. Client and provider suggestions differed in some areas. While providers emphasised structural changes such as increased training on IPV provided by their organisation, clients highlighted the importance of trusting personal relationships with staff to increase client disclosure of IPV experiences. Given the differing opinions of clients and staff, ASOs should consider involving women with histories of IPV in the process of programme and policy development. ASOs have the unique opportunity to provide comprehensive and holistic care by addressing IPV. The extent to which ASOs are able to recognise and address IPV and strategies for increasing this ability warrant greater attention from funders, ASO administrators and researchers.